Preface (Agribusiness, development and the 2030 agenda: interdisciplinary contributions, 2025)
Associate Professor at São Paulo State University "Júlio de Mesquita Filho" (UNESP), Faculty of Sciences and Engineering (FCE), Tupã Campus in the Administration program (09/2013 to present); Permanent Faculty Member of the Graduate Program in Agribusiness and Development (Master's and Doctoral degrees) at FCE/Tupã. Leader and researcher of the Kamby Research Group (GPKamby) "Best Practices in Dairy Farming." Researcher in the CEPEAGRO research group (Research Center in Administration and Agribusiness/UNESP) and the DGE Laboratory (Design Thinking, Management, and Industrial Engineering - UFF/Unesp). Holds a habilitation in Production Management from UNESP (2019). Postdoctoral Fellow from the Graduate Program in Production Engineering and Computational Systems (MESC-ICT) at Fluminense Federal University - UFF (2018). Holds a Bachelor's, Master's, and Ph.D. in Production Engineering from the Methodist University of Piracicaba (UNIMEP). Postgraduate degree in Alcohol and Sugar Management and Production (MBA) from IAT/Fatep. Coordinated and taught Production Engineering courses at private higher education institutions (2008-2013). Conducts research in the areas of Production Management, Quality Management, Supply Chain Management, Production Planning and Control, and Organizational Sustainability.